Analisa Pengaplikasian Sistem Rekam Medis Elektronik di Rumah Sakit Setia Mitra - Garis Gemilang; Indah Kristina; Aji Amarullah (Jurnal Rekam Medis dan Informasi Kesehatan, 2022)
From the observation at Setia Mitra Hospital, there have been issues relating to the appliance of electronic medical record (EMR) system. As we all know, the EMR system is currently starting to be a must use system on every hospital. The advancement of technology has shift the use of paper based medical record to EMR. But since it's still newly developed, the application of the system in a newly applied EMR on a hospital is an interesting topic for review. Therefore the writer has chosen this topic to be the main issue on this research. This research main purpose is to find and identify the application of EMR in Rumah Sakit Setia Mitra. For this research, the writer is using a qualitative descriptive research, in which the data colletion is based on the observation done by the writer and also based on interviews that's done with the medical record staffs, and will be analyzed and compared with theories that already exist as the based accepted method on EMR and it's application. The results of the research done by the writers have found that EMR application at Setia Mitra Hospital is not yet been applied according with the theory that's aready exist, and the mains source of this difference is because the EMR on the hospital's information system is still under heavy development. Therefore, the author has suggested that the completeness of the hospital information system must take priority, especeially regarding it's medical record system need to be pushed into an EMR system, so it can create a much more complete, better and robust health information management at RS Setia Mitra.